Moderate Education Model in Building the Ideology of the Young Generation - Ahmad Mohdlori (TAWASUT, 2025)
This study aims to examine and examine various models of Islamic education carried out in senior high schools. Islamic education is a field of study that must be carried out starting from elementary school to senior high school and even college, with the hope that students have understanding, experience and can practice religious teachings in accordance with Islamic concepts correctly and kaffah based on the Qur'an. an and Hadith. The model in Islamic education can be in the form of Islamic boarding system education, Integrated Islamic education, Islamic boarding school education, Kuttab education, religious education based on life skills. In the development of this model of Islamic religious education, it must be oriented to the philosophy of life in the form of philosophical, etymological and pedagogical. This research is categorized as library research using descriptive qualitative analysis of literature. The data collection technique uses a study of book texts on education and laws and government regulations that contain Islamic education, especially in senior high schools. The analysis used in this research is text content analysis